O convento de S. Domingos e o plano urbano do Porto entre os séculos XIII e XVI - Afonso, José Ferrão (2016)
This paper summarizes the key role that the Dominicans have played in shaping the urban landscape of Porto between the thirteenth and seventeenth centuries, a topic that is a leading issue to our recently published doctoral thesis (Afonso, 2013).